The Veda as Revelation - Chemparathy, George (Journal of Dharma, 2020)
The faithful of every religion ascribe to their Sacred Scriptures a unique sacredness and authority which distinguish them from every other work, religious or secular. From the very beginnings of Hinduism the Hindus have looked upon some texts of their sacred literature, coming under the name of ’Veda’ , as possessing such a unique sacredness and authority. The Hindu thinkers have not only considered them as the norm of their faith and the source of their religious practices but they have also vindicated the singular status of these works even among the Hindu religious literature. They have, in short, ascribed to the Veda a position comparable to that which the Christians ascribe to the Bible and the Muslims to the Qur’an, both of which are considered by their respective faithful as ’revelation’. In this paper we shall study the question whether and in what sense the Veda can be said to be revelation.